Strategy For Preventing Forest and Land Fires in Belitung Regency - Amallia Anggraini (Faculty of Social Science, Universitas Negeri Padang, 2017)
The purpose of this study is to determine the behavior of society and other parties in managing forests and land as well as to formulate strategies to prevent forest and land fire in Belitung Islands Belitung province. This study uses a mixed method by combining descriptive method which is supported by AHP (Analytical Hierarchy Process). From the analysis that has been done, there are five policy priorities that can be applied as the policy strategies to prevent both forest and land fires in Belitung Regency, namely: 1) imposition of discipline the use of fire for land expansion, 2) Tightening surveillance, patrols and surveillance in vulnerable forest burning, 3) Socialization and elucidation to the society about the dangers of forest and land fires, 4) Develop training patterns of forest and land fire prevention, 5) Establish prone areas to fire.